The impressive of geological evidence of Kuala Muda District: a proposal for geotourism products in Kedah, Malaysia - Abd Halim, Mohd Hasfarisham; Said, Mohd Zulhafiz; Ali, Mohd Amin; Masnan, Shyeh Sahibul Karamah; Talib, Nor Khairunnisa; Saidin, Mokhtar (Editura Universitatii din Oradea, 2024)
This study provides primary evidence about the geological features in Kuala Muda district, indicating significant potential for development as a geotourism product. To collect primary data, we conducted survey and mapping activities to gather information about the current condition of 11 geosites, as well as the facilities already in place to facilitate seasonal tourism. In addition, a review of previous scientific research for each geosite is also carried out so that geosite speciality data can be summarized. The study's results have facilitated the creation of 17 tourism packages under the AncKed Sungai Batu Association, encompassing geology, geoarchaeology, biology, history, heritage, and culture tourism products in the Kuala Muda district. Offering tour packages enables the district to conduct knowledgeable tourism activities involving people from all walks of life and ages, with trained locals serving as tour guides. This ensures the preservation of geotourism at its optimal level.